Analisis Spasial Risiko Bencana Kebakaran Hutan Dan Lahan Di Kabupaten Pesawaran - Simarmata, Nirmawana; Nadzir, Zulfikar Adlan; Agustina, Lea Kristi; Wijayanti, Goldie Melinda; Giovani, Muhammad (Jurnal Geografi, Edukasi dan Lingkungan (JGEL), 2025)
Forest and land fires are common natural disasters in Indonesia, impacting ecology, economy, and community welfare. This study aims to calculate the spatial risk of Karhutla in Pesawaran Regency as an initial step in disaster management. The data comes from Landsat 8 (OLI) satellite images, slope maps, road maps, rivers, and land cover of Pesawaran Regency. This disaster risk assessment method refers to Decree from the BNPB Head Number 2 on year 2012 with three risk components in the form of vulnerability, hazard, and capacity indices. The hazard index was analyzed using hazard assessment variables, spatial analysis, and attribute analysis. The index of vulnerability is conducted by analyzing the conditions and characteristics of the community and its environment to calculate which factors reduce the ability to cope with disasters. The capacity index is calculated based on five leading indicators: disaster management rules and institutions, early warning systems and disaster risk assessments, disaster education, essential risk factor reduction, and preparedness development at all levels. The calculated hazard, vulnerability, and capacity indices were then combined to assess the risk level of land and forest fire disasters. An analysis from forest and land fire disaster risk assessment results in Pesawaran Regency shows that majority of the area have a medium risk. The largest sub-district with a low-risk level is in Pandan Island Sub-district with an area of 11,332.6 hectare, and the largest sub-district with a high level is in Tegineneng Sub-district of 11,558.3 hectare area, followed by Gedong Meneng sub-district. These sub-districts could be prioritized for a holistic and integrated scheme to add capacity index by all stakeholders.